2012
DOI: 10.1371/journal.pone.0039086
|View full text |Cite
|
Sign up to set email alerts
|

Betahistine Exerts a Dose-Dependent Effect on Cochlear Stria Vascularis Blood Flow in Guinea Pigs In Vivo

Abstract: ObjectiveBetahistine is a histamine H1-receptor agonist and H3-receptor antagonist that is administered to treat Menière’s disease. Despite widespread use, its pharmacological mode of action has not been entirely elucidated. This study investigated the effect of betahistine on guinea pigs at dosages corresponding to clinically used doses for cochlear microcirculation.MethodsThirty healthy Dunkin-Hartley guinea pigs were randomly assigned to five groups to receive betahistine dihydrochloride in a dose of 1,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 36 publications
1
49
0
3
Order By: Relevance
“…These findings are in line with the literature that suggests that the H 1 -receptor has no effect on betahistine-induced effects on cochlear blood flow [Laurikainen et al, 1993]. However, one more observation should be pointed out here: in previous experiments it has been shown that higher doses of betahistine show a significant yet short-lived drop in mean arterial pressure and cochlear blood flow at the beginning of betahistine infusion [Ihler et al, 2012a]. This initial and brief drop seems to be steeper the high- er the concentration of betahistine [Dziadziola et al, 1999].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in line with the literature that suggests that the H 1 -receptor has no effect on betahistine-induced effects on cochlear blood flow [Laurikainen et al, 1993]. However, one more observation should be pointed out here: in previous experiments it has been shown that higher doses of betahistine show a significant yet short-lived drop in mean arterial pressure and cochlear blood flow at the beginning of betahistine infusion [Ihler et al, 2012a]. This initial and brief drop seems to be steeper the high- er the concentration of betahistine [Dziadziola et al, 1999].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, betahistine could aid in the central-nervous compensation that takes place after a patient has suffered from an attack [Redon et al, 2011]. Lastly, it has been shown that betahistine is capable of increasing cochlear blood flow in animal models and could therefore aid in the reduction of the endolymphatic hydrops [Dziadziola et al, 1999;Laurikainen et al, 2000;Ihler et al, 2012a]. So far, this has been viewed as the most likely mechanism of action in Ménière's disease [Strupp et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of cochlear blood flow is essential for hearing and is important as a treatment strategy for the restoration of hearing loss in humans [38]. Homeostatic regulation of blood flow in the cochlear capillary beds is achieved by the dynamic adjustment of the vascular diameter or “tone” of pre-capillary arteries and arterioles against systemic changes of pressure, nerve and metabolic activity [914].…”
Section: Introductionmentioning
confidence: 99%
“…Betahistine is a strong histaminergic H3 receptor antagonist; this property may account for the increase in CoBF via an increase in histamine release and consequent activation of postsynaptic histaminergic H1 and H2 receptors. Betahistine may also have weak direct effects on these postsynaptic receptors or an effect modulated by other autonomic receptors [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Betahistine is a strong histaminergic H3 receptor antagonist; this property may account for the increase in CoBF via an increase in histamine release and consequent activation of postsynaptic histaminergic H1 and H2 receptors. Betahistine may also have weak direct effects on these postsynaptic receptors or an effect modulated by other autonomic receptors [3] .In this study, the protective effect of betahistine on noise-induced hearing loss (NIHL) was evaluated for the first time using scanning electron microscopy (SEM) and distortion product otoacoustic emission (DPOAE) data. Preyer's reflexes and normal tympanic membranes were used for these experiments.…”
mentioning
confidence: 99%